Diacerein-Loaded Hyaluosomes as a Dual-Function Platform for Osteoarthritis Management via Intra-Articular Injection: In Vitro Characterization and In Vivo Assessment in a Rat Model - Nouran O. Eladawy; Nadia M. Morsi; Rehab N. Shamma (MDPI AG, 2021)
The application of intra-articular injections in osteoarthritis management has gained great attention lately. In this work, novel intra-articular injectable hyaluronic acid gel-core vesicles (hyaluosomes) loaded with diacerein (DCN), a structural modifying osteoarthritis drug, were developed. A full factorial design was employed to study the effect of different formulation parameters on the drug entrapment efficiency, particle size, and zeta potential. Results showed that the prepared optimized DCN- loaded hyaluosomes were able to achieve high entrapment (90.7%) with a small size (310 nm). The morphology of the optimized hyaluosomes was further examined using TEM, and revealed spherical shaped vesicles with hyaluronic acid in the core. Furthermore, the ability of the prepared DCN-loaded hyaluosomes to improve the in vivo inflammatory condition, and deterioration of cartilage in rats (injected with antigen to induce arthritis) following intra-articular injection was assessed, and revealed superior function on preventing cartilage damage, and inflammation. The inflammatory activity assessed by measuring the rat's plasma TNF-α and IL-1b levels, revealed significant elevation in the untreated group as compared to the treated groups. The obtained results show that the prepared DCN-loaded hyaluosomes would represent a step forward in the design of novel intra articular injection for management of osteoarthritis.